Pengembangan Model Inovasi dan Kreativitas Keilmuan Pendidikan Islam Anak Usia Dini - Kurniawan, Heru; Fakhrudin, Asef Umar (Generasi Emas, 2023)
One of the important tasks of the study program is to carry out educational innovation and creativity. This research was conducted to find a model for developing scientific innovation and creativity in the study program. The research method used is field research in which the data is identified through interviews, documentation, and observation. The results of the research are First, PIAUD Study Program students realize the importance of scientific innovation and creativity in early childhood education because it is based on the scientific reality of early childhood education that requires creativity, the demands of institutional work that want creative graduates, and scientific opportunities in early childhood education that have market opportunities. good to develop. Second, the model for developing scientific innovation and creativity in early childhood education is carried out through intensive collaboration between lecturers and students which is realized by institutional mentoring of lecturers with the PIAUD Studio community which is established and developed according to students' interests and talents in the scientific field of early childhood education. With this model, PIAUD Study Program students have good creativity and innovation as evidenced by various achievements at the national level in innovation and creativity competitions for early childhood education students.